PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEPATU WATCHOUT DI MATAHARI BCS MALL BATAM - Febrizal; Asron Saputra, S.E., M.Si. (SCIENTIA JOURNAL, 2022)
ABSTRACT The purpose of this study was to analyze the effect of service quality and promotion on purchasing decisions for watchout shoes at Mata Hari BCS Mall Batam. This type of survey is a quantitative research that uses purposive sampling as many as 260 respondents and examined in detail using SPSS version 25, where t count 9,325 > t Table 1,969 which is a significant value known to be 0,000 < 0,05. This means that service quality has an influence and is important in making purchasing decisions. It is known that the t count for promotion is 8,672 > t table of 1.969 and the significance value is 0,000 < 0,05. This means that promotions are effective and important for purchasing decisions. Second, between service quality and promotion, there is an important (together) impact on the decision to buy watchout shoes at Mata Hari BCS Mall Batam. This can be seen from the F value of 309.960 (F count) > 2.64 (Table F). Significant value 0,000 < 0,05. Keywords: Service Quality;Promotion and Buying Decision